Eidolonic Optometry: A Tribute to Dr. Mort Davis (Parts 4 & 5). (Optometry & Visual Performance, 2024)
The following two articles appeared as a serial from late 1986 and throught 1987 in the Curriculum distributed by the Optometric Extension Program Foundation. This series, “adds to the concepts developed by A.M. Skeffington, OD, for describing the emergent in his model of vision. The series will be published in its entirety throughout Volume 12 as a tribute to Dr. Mort Davis, who passed last year. We hope you enjoy his brillaince.